2018
DOI: 10.1103/physrevb.97.125103
|View full text |Cite
|
Sign up to set email alerts
|

Pauli metallic ground state in Hubbard clusters with Rashba spin-orbit coupling

Abstract: We study the "phase diagram" of a Hubbard plaquette with Rashba spin-orbit coupling. We show that the peculiar way in which Rashba coupling breaks the spin-rotational symmetry of the Hubbard model allows a mixing of singlet and triplet components in the ground-state that slows down and it changes the nature of the Mott transition and of the Mott insulating phases. arXiv:1712.05618v2 [cond-mat.str-el]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…We need two further properties: the charge-current density ij between distinct sites i and j (where, in the prefactor, i ≡ √−1) and the spin-current density μ ij (μ = x , y , z ) …”
Section: Theorymentioning
confidence: 99%
“…We need two further properties: the charge-current density ij between distinct sites i and j (where, in the prefactor, i ≡ √−1) and the spin-current density μ ij (μ = x , y , z ) …”
Section: Theorymentioning
confidence: 99%
“…In summary, the results shown here demonstrate the effect of local lattice fluctuations and consequent local symmetry breaking in driving a universal and intrinsic spin-orbit coupling in hole-doped Bi-based cuprates. Recent theoretical works have proposed that SOC could play an important role in cuprate physics, by stabilizing, for example, the onset of a metallic phase out of an antiferromagnetic insulating background, as recently shown in the case of a Hubbard plaquette [36], or by enhancing the formation of a charge density wave (CDW) and pseudogap phase [37], ferromagnetic ordering [38,39], and even superconductivity [40], in effect turning on different components for the symmetry of the order parameter [11]. In the underdoped regime, d-density wave [41] and loop-current order [42] models used to describe the pseudogap phase, both rely on a non-zero SOC that couples the orbital current with the spin channel.…”
mentioning
confidence: 93%
“…In Ref. [25] we showed that in small Hubbard clusters the presence of RSOC contrasts the localization effect of the interaction and favors a metallic ground-state through a mixing between singlet and triplet components which enables a new screening mechanism of local interactions. We called this new metallic state Pauli metal.…”
mentioning
confidence: 99%
“…In this work we choose a four-site plaquette which, as stressed in Ref. [25], is the minimal cluster where the non-abelian gauge structure of Rashba coupling can emerge. With this choice, our study encompasses the Pauli screening mechanism discussed in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation